2004
DOI: 10.1677/joe.0.1800469
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the expression of prostaglandin E and F synthases at induced and spontaneous labour onset in the sheep

Abstract: The differential production of prostaglandin (PG) F 2 and PGE 2 within the uterine compartment may play a role in controlling myometrial contraction. We hypothesized that the enzymes downstream of PG endoperoxide synthase-2 (PGHS-2) determine the ratio of PGF 2 and PGE 2 in the utero-ovarian vein plasma and the time of normal and preterm labour onset. The aim of this study was to simultaneously determine the expression of PGF and PGE synthases (PGFS and PGES) in gestational tissues at spontaneous and induced-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…A number of studies of the expression of mPGES-1 in fetal membranes, placenta, and myometrium during pregnancy and labor in humans and other species have been reported (Giannoulias et al, 2002;Martin et al, 2002;Alfaidy et al, 2003;Meadows et al, 2003Meadows et al, , 2004 MPGES-1: A NOVEL THERAPEUTIC TARGET Sun et al, 2003;Palliser et al, 2004). PGE 2 is the major vasodilator eicosanoid of the ductus arteriosus and has been suggested to be of importance for maintenance of a patent ductus arteriosus perinatally.…”
Section: Reproductive Endocrinologymentioning
confidence: 99%
“…A number of studies of the expression of mPGES-1 in fetal membranes, placenta, and myometrium during pregnancy and labor in humans and other species have been reported (Giannoulias et al, 2002;Martin et al, 2002;Alfaidy et al, 2003;Meadows et al, 2003Meadows et al, , 2004 MPGES-1: A NOVEL THERAPEUTIC TARGET Sun et al, 2003;Palliser et al, 2004). PGE 2 is the major vasodilator eicosanoid of the ductus arteriosus and has been suggested to be of importance for maintenance of a patent ductus arteriosus perinatally.…”
Section: Reproductive Endocrinologymentioning
confidence: 99%
“…The cascade of events precipitating labour remains unclear but it is proposed that the myometrium becomes primed to contract before the initiation of labour. This is caused by activation of a series of genes, that encode a number of contractionassociated proteins (Challis and Lye, 1994), including the oxytocin receptor, the prostaglandin F receptor and the gap junction protein connexin43 (Cx43) (Imamura et al, 2000;Palliser et al, 2004;Lye, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…In corpus luteum, PGFS were localized in the large luteal cells and IFNincreased PGES expression (~2-fold) but not PGFS. Palliser et al (2004) demonstrated that the expression of PGFS increased in the placentome following dexamethasone induced and spontaneous labour onset in the sheep. Mondal (2009) reported that the expression of PGFSL-2 mRNA could not be detected in buffalo uterine endometrium at any stage of estrous cycle.…”
Section: Prostaglandin F Synthase (Pgfs)mentioning
confidence: 96%